2020
DOI: 10.1302/0301-620x.102b9.bjj-2020-0340.r1
|View full text |Cite
|
Sign up to set email alerts
|

Does screw position matter for guided growth in cerebral palsy hips?

Abstract: Aims Guided growth has been used to treat coxa valga for cerebral palsy (CP) children. However, there has been no study on the optimal position of screw application. In this paper we have investigated the influence of screw position on the outcomes of guided growth. Methods We retrospectively analyzed 61 hips in 32 CP children who underwent proximal femoral hemi epiphysiodesis between July 2012 and September 2017. The hips were divided into two groups according to the transphyseal position of the screw in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…The physis growing off the screw remains a disadvantage of guided growth because of the need for another operation to advance the screw. Hsu et al 25 showed that the transphyseal location of the screw can influence the revision rate in guided growth of the proximal femur. Future studies are needed to clarify whether the screw position plays a role in the context of Kalamchi type II AVN in children with DDH.…”
Section: Discussionmentioning
confidence: 99%
“…The physis growing off the screw remains a disadvantage of guided growth because of the need for another operation to advance the screw. Hsu et al 25 showed that the transphyseal location of the screw can influence the revision rate in guided growth of the proximal femur. Future studies are needed to clarify whether the screw position plays a role in the context of Kalamchi type II AVN in children with DDH.…”
Section: Discussionmentioning
confidence: 99%
“…In children with CP, proximal femoral guided growth (PFGG) with medial screw hemiepiphysiodesis has been shown to decrease the head shaft angle and Reimer's migration percentage (RMP); and decrease the need for subsequent skeletal hip reconstructive surgery. [8][9][10][11] The indications, surgical technique, postoperative management, and potential pitfalls of this relatively new procedure are considered below.…”
Section: Key Conceptsmentioning
confidence: 99%
“…There is no consensus in the literature regarding optimal screw diameter, with reported screw sizes ranging from 4.0 to 7.3 mm. [8][9][10][11] In most cases, a 4.5 mm screw is ideal, given the size of the femoral neck and head in children with CP who are appropriate candidates for PFGG. A fully threaded cannulated screw is preferred to facilitate screw exchange/removal if indicated.…”
Section: Jposnamentioning
confidence: 99%
See 2 more Smart Citations